Metal Ion-Driven Assembly of Cd(II) Coordination Polymer Constructed by Asymmetric Diphenic acid and Imidazole-Containing Ligand: Syntheses, Crystal Structures and Luminescent Properties - Tang*, Yuhai; Cui, Xiangju (Asian Journal of Chemistry, 2014)
A new metal coordination polymer, [Cd(bpdc)(L)0.5](1) [H2bpdc = biphenyl-2,4'-dicarboxylic acid and L = 1,4-bis(2-methyl imidazol-3-ium-1-yl)biphenyl], has been synthesized and characterized by single-crystal X-ray diffraction, elemental analysis and IR spectra. Complex [Cd(bpdc)(L)0.5](1), is, triclinicspace group P-1 with a = 8.673 (5) Å, b = 9.658 (5) Å, c = 11.493 (5) Å, b = 85.169 (5)°,V = 917.1 (8)Å3, Z = 1, Mr = 471.75, Dc = 1.708 g/cm3, F(000) = 470 and μ = 1.221 mm-1. Complex 1 features a 2D sql topological net.